2000
DOI: 10.1053/eupc.2000.0091
|View full text |Cite
|
Sign up to set email alerts
|

Identification of post-myocardial infarction patients prone to ventricular tachycardia using time–frequency analysis of QRS and ST segments

Abstract: In post-myocardial infarction patients, orthogonal wavelet transforms can detect alterations in high-frequency components within the QRS and ST segment. Our findings support the view that wavelet-related parameters are more relevant than those of the time domain method in predicting subsequent malignant tachyarrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The time-frequency data of each QRS complex were collected using the Wavelet transform (Morlet wavelet). According to previous definitions of high frequency content in other works [ 14 , 15 , 16 , 17 ], data were analyzed in the defined range of high frequencies (85–130 Hz), with an upper period of 11.5 ms and lower period of 7.7 ms ( Figure 3 A). A temporal definition of 1 kHz and a frequency resolution of 1/125 suboctaves were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time-frequency data of each QRS complex were collected using the Wavelet transform (Morlet wavelet). According to previous definitions of high frequency content in other works [ 14 , 15 , 16 , 17 ], data were analyzed in the defined range of high frequencies (85–130 Hz), with an upper period of 11.5 ms and lower period of 7.7 ms ( Figure 3 A). A temporal definition of 1 kHz and a frequency resolution of 1/125 suboctaves were used.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have demonstrated a robust link between QRS fragmentation and late potentials [ 14 ]. Overall, fragmentation would represent a more prominent phenomenon that will allow for their identification by visual inspection of the time domain record of the QRS complex, while less prominent forms will be masked within the total energy/voltage of the normal myocardium, thus requiring signal processing for appropriate identification.…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis of 856 post-infarction patients enrolled in the MADIT-II trial, PRD was shown to be an independent predictor of SCD (adjusted HR = 1.40; p = 0.003), suggesting that assessment of repolarization dynamics can be used for SCD risk stratification in IHD patients [ 15 ]. Late potentials (LPs), detecting alterations in high-frequency components within the QRS and ST segment, can identify IHD patients with increased risk for VA or SCD [ 16 ]. Further trials are ongoing to validate these scores and to employ machine learning tools to the ECG for advanced risk stratification.…”
Section: Advanced Analysis Of Ecgmentioning
confidence: 99%
“…The most obvious and not yet fully characterized physiological factor influencing the VR is the HR. In clinical studies, power-law models QTc(i )Z aCb!RR(iK1) g are used despite the fact that the QT-RR relationship is described as a subject-dependent phenomenon (Couderc et al 2000). Fridericia's (QTcZQT!RR K1/3 ) and Bazett's (QTcZQT!RR K1/2 ) are the most common examples of rate correction formulae, where RR is expressed in seconds and is the interval from the beats prior to the QT interval.…”
Section: (I) Cardiac Repolarization and Heart Ratementioning
confidence: 99%